PENGARUH INTELLECTUAL CAPITAL, INVESTMENT OPPORTUNITY SET, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Ardhiestadion, Alexandra; Suzan, Leny (LPPM Universitas Bina Bangsa, 2024)
The purpose of this study is to ascertain intellectual capital, investment opportunity set, also dividend policy on firm value in food and beverage (F&B) sub-sector manufacturing companies registered on the Indonesia Stock Exchange in 2019-2022. The object of this study is manufacturing companies in the F&B sub-sector registered on the Indonesia Stock Exchange in 2019-2022. The sample untilized in this purchase was 18 companies with a research period of 4 years with 72 data processed using purposive sampling techniques. This study employs descriptive statistical analysis methods, also panel data regression analysis. From the outcomes of this study, it was gained that these three variables have a joint impact on the company's value. Meanwhile, intellectual capita, also dividend policies have a negative impact on each. Meanwhile, the investment opportunity set has a positive impact on the company's value